In Vitro Pharmacological Profile of a New Small Molecule Bradykinin B2 Receptor Antagonist - Lesage, Anne; Gibson, Christoph; Marceau, François; Ambrosi, Horst-Dieter; Saupe, Jörn; Katzer, Werner; Loenders, Brigitte; Charest-Morin, Xavier; Knolle, Jochen (Frontiers in Pharmacology, 2020)
We here report the discovery and early characterization of Compound 3, a representative of a novel class of small molecule bradykinin (BK) B2 receptor antagonists, and its superior profile to the prior art B2 receptor antagonists Compound 1 and Compound 2. Compound 3, Compound 2 and Compound 1 are highly potent antagonists of the human recombinant B2 receptor (Kb values 0.24, 0.95 and 1.24 nM, respectively, calcium mobilization assay). Compound 3 is more potent than the prior art compounds and icatibant in this assay (Kb icatibant 2.81 nM). The compounds also potently inhibit BK-induced contraction of endogenous B2 receptors in a human isolated umbilical vein bioassay. The potencies of Compound 3, Compound 2, Compound 1 and icatibant are (pA2 values) 9.67, 9.02, 8.58, and 8.06 (i.e. 0.21, 0.95, 2.63 and 8.71 nM), respectively. Compound 3 and Compound 2 were further characterized. They inhibit BK-induced c-Fos signaling and internalization of recombinant human B2 receptors in HEK293 cells, and do not antagonize the venous effects mediated by other G protein-coupled receptors in the umbilical vein model, including the bradykinin B1 receptor. Antagonist potency of Compound 3 at cloned cynomolgus monkey, dog, rat and mouse B2 receptors revealed species selectivity, with a high antagonist potency for human and monkey B2 receptors, but several hundred-fold lower potency for the other B2 receptors. The in vitro off-target profile of Compound 3 demonstrates a high degree of selectivity over a wide range of molecular targets, including the bradykinin B1 receptor. Compound 3 showed a lower intrinsic clearance in the microsomal stability assay than the prior art compounds. With an efflux ratio of 1.0 in the Caco-2 permeability assay Compound 3 is predicted to be not a substrate of efflux pumps. In conclusion, we discovered a novel chemical class of highly selective and very potent B2 receptor antagonists, as exemplified by Compound 3. The compound showed excellent absorption in the Caco-2 assay, predictive of good oral bioavailability, and favourable metabolic stability in liver microsomes. Further structure-activity relationships and preclinical characterization will allow selection of clinical candidates for the treatment of patients with hereditary angioedema or BK-mediated disorders.